Pendampingan Implementasi Strategi Digital Marketing untuk Meningkatkan Pendapatan Warung Komunal di Wisata Jalan Tol Kahyangan - Ratnasari, Emma Dwi; Retnosari , Retnosari; Novitaningtyas , Ivo; Nurcahya, Yulida Army; Sunaningsih , Suci Nasehati (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service initiative aims to improve the performance of communal stalls in the Kahyangan Highway tourist area, Magelang Regency through digital marketing strategies. This activity, which was implemented on May 15, 2024, involved stall owners, academics from Tidar University, and digital marketing practitioners. The program focused on intensive training related to website development, social media management, and augmented reality technology. The results showed a significant increase in market visibility and customer traffic, leading to increased sales. The program also provided new insights to the warung owners on the importance of digital marketing for business competitiveness. Despite challenges such as limited access to advanced technology and the need for ongoing technical support, the program confirmed the great potential of digital marketing strategies to empower community-based tourism enterprises. The importance of continuous collaboration between academics and community stakeholders was also emphasized to support sustainable local economic development.